NATURAL INFECTION OF Tobacco mosaic virus ON BUTTERNUT SQUASH IN BALI, INDONESIA - Listihani, Listihani; Selangga , Dewa Gede Wiryangga; Sutrawati, Mimi (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2021)
Natural infection of Tobacco mosaic virus on butternut squash in Bali, Indonesia. Tobacco mosaic virus (TMV) was a newly emerging virus infecting cucumbers in Indonesia since 2017. The mosaic disease caused by TMV potentially caused yield loss cucumber in Java. In 2019, mosaic symptoms were observed in butternut squash plants in Bali and molecular detection using universal primer of Tobamovirus indicated the presence of TMV infection. Further research was conducted to determine molecular characteristics of TMV on butternut squash plants in Bali. Specific DNA bands of Tobamovirus were amplified using reverse transcription polymerase chain reaction method, followed by DNA sequencing. The DNA were successfully amplified from CP Tobamovirus using universal primers from several butternut squash samples, i.e. Denpasar, Gianyar, Buleleng, and Karangasem Districts. The homology analysis of nucleotide and amino acid sequences of TMV among isolates from Denpasar, Gianyar, Buleleng, and Karangasem Districts was ranged between 95.6 – 97.7% and 98.1 – 99.4%, respectively. This indicated that low genetic diversity of TMV among Bali isolates. The highest homology of corresponding sequences of TMV isolates from Denpasar, Gianyar, Buleleng, and Karangasem Districts was closely related to TMV Kediri-Indonesia isolate on cucumber plant. Correspondingly, the phylogenetic analysis showed that TMV Bali isolates were categorized into same cluster with Kediri-Indonesia isolates. This was the first report of TMV on butternut squash in Indonesia.